Effects of gender and age on prevalence of cholelithiasis in patients with chronic HCV infection: A community-based cross-sectional study in an HCV-hyperendemic area. Issue 22 (June 2018) - Hu, Jing-Hong; Chen, Mei-Yen; Yeh, Chau-Ting; Chiu, Wen-Nan; Chiang, Ming-shih; Chang, Ming-Ling
Abstract : Abstract: This study investigated the effects of age and gender on the prevalence of cholelithiasis in patients with chronic HCV infection. Demographic and clinical data of 8489 subjects (3671 males, 4818 females; mean age 47.5 years) receiving township-wide health examinations between September 2012 and August 2013 were analyzed. The main endpoint was prevalence of cholelithiasis. Risk factors (age, gender, body mass index, concomitant diseases, lifestyle, laboratory parameters, and HCV status) were evaluated. Univariate and multivariate logistic regression analyses were performed to identify associations between cholelithiasis and variables. Cholelithiasis was more prevalent among HCV subjects than non-HCV subjects (females: 8.1% vs 4.2%; males: 9.1% vs 3.9%; both P < .001); rates ranged from 5.6% to 8.3% in females and 4.7% to 10.6% in males. HCV status and age were associated with cholelithiasis occurrence (OR = 2.17 for HCV vs non-HCV; OR = 2.44, 3.54 for age 45–55, and >55 vs <45 years; all P < .05). Multivariate analysis showed a significant association between cholelithiasis and age/sex interaction terms (OR = 0.517 for age >55 vs <45 for sex; P = .011). Cholelithiasis prevalence was significantly associated between age and sex interaction terms but not anymore if considering positive HCV status. All noninvasive tests for liver fibrosis were associated with cholelithiasis but only fibrosis-4 index was significantly associated (OR = 1.28, P = .019). Age, gender, and HCV infection are associated with increased risk and prevalence of cholelithiasis. After age of 55 years, cholelithiasis is more prevalent among HCV-positive males than females. Females of age 55 and more may be protected against cholelithiasis as sex hormones decrease.